Clinical relevance of serum ionized magnesium concentration in dogs with myxomatous mitral valve disease - Ock‐Kyu Kim; Keon Kim; Sinwook Park; Hayoung Yang; Hyunwoo Kim; Woong‐Bin Ro; Chang‐Min Lee (Journal of Veterinary Internal Medicine, 2024)
Abstract Background Hypomagnesemia is associated with a poor prognosis in humans with congestive heart failure (CHF), but studies in veterinary medicine are limited. Hypothesis Serum ionized magnesium concentration [iMg2+] would decrease as CHF progresses compared with the initial diagnostic levels and that lower [iMg2+] would be negatively associated with prognosis in dogs with CHF. Animals A total of 181 client‐owned dogs with myxomatous mitral valve disease (MMVD) were included. They were classified into the preclinical stage (NO‐CHF, n = 108), stage C (n = 42), and stage D (n = 31) based on the American College of Veterinary Internal Medicine MMVD classification. Methods This is a retrospective study from 2 referral centers. The [iMg2+] was compared among the NO‐CHF, stage C, and stage D groups. Kaplan‐Meier curves and the log‐rank test were used to compare the incidence of death between groups. Multivariable Cox regression analysis was used to estimate the association of hypomagnesemia with the death. Results In the stage D group, the [iMg2+] was lower than that in the NO‐CHF (P < .0001) and stage C groups (P < .003). In the Kaplan‐Meier survival analysis, the 1‐year cumulative survival rate in hypomagnesemic dogs was 53% compared with 91.5% in normomagnesemic dogs (log‐rank test, P < .0001). In the multivariable Cox analysis, lower concentration of [K+] and [iMg2+], along with higher Evel, were associated with negative prognoses. Specifically, hypomagnesemia was associated with an approximately 4‐fold increased risk of death (hazard ratio = 4.015; 95% confidence interval, 1.537‐10.488; P = .005). Conclusions and Clinical Importance Assessing the [iMg2+] might serve as a potential marker for estimating the severity and prognosis indirectly in dogs with MMVD. Combining [iMg2+] measurement with other diagnostic methods, such as echocardiography, could improve the prognostic evaluation of MMVD in dogs.